Pengembangan Metode Analisis Agen Pengatur Keasaman Pakan Ternak Menggunakan Metode Kromatografi Cair Kinerja Tinggi - Asih, Ninis Kurnia; Harmita, Harmita; Maggadani, Baitha Palanggatan (UI Scholars Hub, 2017)
Quantitative analysis of organic acid in acidifier product is needed to maintain product effectiveness in repressing microbial growth and lowering feed and gastrointestinal tract pH. The aim of this research is determining the level of formic and lactic acid in two acidifiers from the market. Analysis were performed using reversed phase High Performance Liquid Chromatography (HPLC) with LiChrospher® 100 RP-18 column (250 x 4.0 mm, 5μm, Merck), buffer potassium dihydrogenphosphate 50 mM-TEA 0,5% pH 4,00 as mobile phase and flow rate 0,6 mL/min. Wavelength used in the analysis was 214 nm. Validation methods provide results of recovery by 98.02%-101.97% for formic acid and 97.09%-102.78% for lactic acid, RSD <0.59% for formic acid and 1.28% for lactic acid, LOD 63.05 µg/mL for formic acid 4.55 µg/mL for lactic acid, LOQ 210.16 µg/mL for formic acid and LOD 15.18 µg/mL for lactic acid. The analysis method gives linearity in the range of 439.2 -1764.61 µg/mL for formic acid with correlation coefficient (r) 0.9992 while lactic acid linearity range was 47.88 µg/mL-193.44 g/mL with a correlation coefficient (r) 0.9994. Conformity product A to its label provides the results of 108.19%-109.82% formic acid and 156.88%-167.90% lactic acid whereas the result for product B were 101.65%-109.95% formic acid and 151.10%-172.82% lactic acid.